Antibody-guided nanomedicines as novel breakthrough therapeutic, diagnostic and theranostic tools. (29th July 2019) - Farahavar, Ghazal; Abolmaali, Samira Sadat; Gholijani, Nasser; Nejatollahi, Foroogh
Abstract : Antibody-decorated nanomaterials as emerging platforms for therapeutic, diagnostic and theranostic applications. Abstract : Recent advances in nanotechnology, such as the development of various types of nanoparticles and hybrid nanomaterials, have revolutionized nanomedicine. The small size, customizable surface, enhanced solubility, and multi-functionality endow the nanoparticles with an ability to interact with complex cellular and biological functions in new ways. Furthermore, these systems can deliver drugs to specific tissues and provide a targeted therapy. For this purpose, different categories of molecules, particularly antibodies, have been used as ligands. Antibody-conjugated nanomaterials can significantly enhance the efficiency of nanomedicines, especially in the field of cancer. This review is focused on three major medical applications of antibody-conjugated nanomaterials, namely, therapeutic, diagnostic and theranostic applications. To provide comprehensive information on the topic and an overview of these hybrid nanomaterials for biomedical applications, a brief summary of nanomaterials and antibodies is given. Moreover, the review has depicted the potential applications of antibody-conjugated nanomaterials in different fields and their capabilities to empower nanomedicine, particularly in relation to the treatment and detection of malignancies.